The Clinical Expression and Implication of Plasma miRNAs in Patients with Atrial Fibrillation - Dantas, Kamilo Mesquita; Rezende, Heitor Tomé; Silva Junior, Antônio Menezes da; Sobrinho, Hermínio; de Oliveira, Pedro Paulo Clark (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Introduction: circulating miRNA were identified as potential biomarkers in cardiac arrhythmias. It is intended to evaluate, in patients with atrial fibrillation (AF), the expression of miRNAs in plasma, their clinical repercussion and their prognostic factor. Materials and Methods: PubMed, Cochrane and Google Scholar platforms were used as a data source. Eligibility criteria: miRNAs as direct biomarkers in the clinical expression of AF; all languages. Last search: 19/09/2019; studies involving other comorbidities were excluded; pharmacological focus; in animals, in patients already submitted to cardiac procedures and review articles. Plasma collection and storage, RNA isolation, data analysis, realtime PCR, miRNA target prediction and statistical analysis were performed in the studies. Results: The studies generated n = 332 patients: with AF and control group. In patients with AF there was an increase in the expression of miR-1266, miR-4279, miR- 892a, miR-3149, miR-155, miR-146b5p, miR-19b and a reduction in miR-3171, miR-3664-5p and miRNA -150. Discussion: it was noted that the regulation of inflammatory mediators, ion channels and cardiac morphophysiology are related to the expression of miRNA. Conclusion: Therefore, the levels of changes in miRNAs may reflect the severity of the clinical and pathophysiological progression of AF, and can be used as predictors of AF.